Strength analysis of an oblique section according to elastic-plastic characteristics/Įstrižo pjūvio stiprumo apskaičiavimas įvertinant tampriąsias ir plastines medžiagos deformacijas - Svetlauskas, Vytautas A. (Journal of Civil Engineering and Management, 1999)
The equilibrium of a reinforced concrete members part limited by one oblique and two vertical sections and exposed to shear forces is under consideration. Three equilibrium equations system of the forces of this reinforced concrete part and the condition of its failure are given. The assumptions and the possibility of solution of this system are considered. The analysis of the values of oblique section forces is presented. The position of a permanent dangerous oblique section and the height of compression concrete layer on its peak, ie the position of weakest design oblique section, is discussed. The bearing capacity of an oblique section is analysed. The recommendations presented are universal. If oblique forces can be neglected, the formulae can be used for structural analysis of normal section in a pure bending zone.Article in Lithuanian.First Published Online: 26 Jul 2012